Effect of natural farming on soil fertility and carbon sequestration: A case study from Eastern India - Pradipta, M; Debasis, P; Jibanjit, S; Dwarika, M D; Prasannajit, M; Avijit, H; Bichhinna, M R; Balia, M; Tapan, K P; Amit, P; et al. (Plant Science Today, 2026)
Soil degradation from excessive chemical inputs threatens agricultural sustainability, particularly in coastal ecosystems of Odisha. This study evaluated the effects of Natural Farming (NF) and Conventional Farming (CF) on soil fertility, carbon sequestration, microbial populations, crop yield and economics in vegetable cultivation (brinjal, okra, tomato) at Krishi Vigyan Kendra (KVK) Jagatsinghpur during rabi 2022-2023. NF involved the use of Jeevamrit, Beejamrit, mulching, Ghanajeevamrit, Neemaster, Bramhastra, Agniastra while CF followed standard recommended practices. Soil samples (0–15 cm) were analyzed before and after harvest for physical, chemical and biological parameters. NF increased soil pH, improved soil organic carbon (SOC) (0.43 % → 0.45 %) and enhanced nitrogen availability (6.46 % increase), while CF showed a slight SOC decline and lower N improvement. SOC stock increased by 0.16–0.62 Mg/ha under NF but declined by 0.25 to 2.49 Mg/ha under CF. NF significantly increased bacterial (47.5 %), fungal (40.12 %) and actinomycetes (70.4 %) populations over CF. Crop yields under NF were marginally lower, but reduced cultivation costs led to slightly higher benefit-cost ratios (B:C) in all crops. Correlation analysis revealed significant interrelations among soil properties, with carbon sequestration negatively correlated with pH (r = -0.85*). The results demonstrate NF’s potential to improve soil health, enhance carbon sequestration and maintain profitability in coastal vegetable systems, supporting its promotion as a sustainable alternative to CF in climatic vulnerable coastal areas in Odisha and similar agro-climatic regions of the country and beyond.